Impact of Demand of a Social Tourism in the Sustainability of the Activity in the Locality of el Quisco, Province of San Antonio - Chile [Impacto de la Demanda de Un Turismo Social en la Sustentabilidad de la Actividad en el Balneario de el Quisco, Provincia de San Antonio - Chile] - Portal-Valenzuela, B; Espinoza-Ramirez, J (Instituto de Geografia, 2014)
Every summer Chile s Central Coast undergoes the effects of social tourism, as a vast number of low-income visitors arrive from Chile s most densely populated areas in the Central Zone. Despite congestion and saturation of available touristic resources, the number of visitors increases every year, contravening classic touristic demand models that define migration to less congested resources as the outcome of congestion. This analysis will be focused on El Quisco beach, located at Valparaiso s Region, a touristic destination that clearly represents this process of mass tourism socialization. The goal of this research is to understand the demand composition that social tourism generates, by determining its nature and identifying the factors that define its behavior. These factors are related to the visitor s origin, displacement, permanence, loyalty, social bonds, gender, income, consumption capacity, and to the degree of satisfaction regarding touristic supplies such as beaches, equipment, and infrastructure. Understanding this demand behavior it is key to develop policies enabling the planning of sustainable social tourism, and allowing for low-income families to access high-quality resources.